2014
DOI: 10.5194/angeo-32-1093-2014
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of the substructure of a flux transfer event: analysis of high-time-resolution particle data

Abstract: Abstract. Flux transfer events (FTEs) are signatures of transient reconnection at the dayside magnetopause, transporting flux from the dayside of the magnetosphere into the magnetotail lobes. They have previously been observed to contain a combination of magnetosheath and magnetospheric plasma. On 12 February 2007, the four Cluster spacecraft were widely separated across the magnetopause and observed a crater-like FTE as they crossed the Earth's dayside magnetopause through its low-latitude boundary layer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 82 publications
(120 reference statements)
2
18
1
Order By: Relevance
“…In this event, for a few seconds, the magnetic field became closely aligned to the spin axis of the Cluster satellites. As a result, observations of the particle distribution at each spin azimuth correspond to a 0°–180° PAD, which provides us with a unique opportunity to study the dynamic plasma features on the DF with continuous 1/4 s resolution [ Khotyaintsev et al , ; Schwartz et al , ; Varsani et al , ]. For the first time, we report the substructures of ion and electron populations on the DF and show details that are not in the spin‐resolution observations.…”
Section: Introductioncontrasting
confidence: 95%
“…In this event, for a few seconds, the magnetic field became closely aligned to the spin axis of the Cluster satellites. As a result, observations of the particle distribution at each spin azimuth correspond to a 0°–180° PAD, which provides us with a unique opportunity to study the dynamic plasma features on the DF with continuous 1/4 s resolution [ Khotyaintsev et al , ; Schwartz et al , ; Varsani et al , ]. For the first time, we report the substructures of ion and electron populations on the DF and show details that are not in the spin‐resolution observations.…”
Section: Introductioncontrasting
confidence: 95%
“…Heated isotropic magnetosheath electrons populate the core flux ropes ( Figure 3Dg) and lead to a local minimum in density and flux, similar to previous observations [Varsani et al, 2014]. Figure 3Dh shows a disturbed distribution in coincidence with the electric field burst described in section 3 (black arrows in Figures 1e and 1f).…”
Section: Interiorsupporting
confidence: 84%
“…Owen et al [2001] used Cluster observations to define the magnetic field connectivity inferred from the magnetic field and electron signatures. Varsani et al [2014] also investigated the multilayer interior and surrounding structures of a crater FTE based on the electron pitch angles using 125 ms observations of Cluster-PEACE measurements assuming that the electrons were gyrotropic. Owen et al [2008] identified the boundary layer of crater FTEs that features accelerated magnetosheath electrons and injected magnetosheath ions and related the layer to a separatrix region of reconnected flux tubes.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed analysis of the characteristics of the plasma inside the FTEs can help to distinguish among the various generation mechanisms [Lockwood and Hapgood, 1998;Varsani et al, 2014]. Moreover, also the relation of the FTEs with reconnection jets can give important indications to understand the origin of the FTEs.…”
Section: Introductionmentioning
confidence: 99%